ANALISIS KEMAMPUAN LITERASI SAINS PESERTA DIDIK KELAS XI FASE F DI SMA NEGERI 1 ANGKOLA BARAT PADA PEMBELAJARAN BIOLOGI - Yudha Irawan Siregar, Aulia; Hijrah Selaras, Ganda (Universitas Cokroaminoto Palopo, 2025)
Learning is very important for students to prepare a generation that is able to adapt and compete in the era of globalization. The learning concept needed by students in the current era of globalization is 21st century learning. 21st century learning aims to encourage students to have skills that support students to think responsively and be able to compete in the current era of globalization. In 21st century learning, students not only improve learning outcomes, but also the ability to understand and use scientific knowledge information in daily life. This ability is called science literacy. The purpose of this study is to determine the science literacy ability of students in class XI Phase F at SMA Negeri 1 Angkola Barat. The research conducted is a descriptive research, to analyze and describe the science literacy skills of grade XI students at SMA Negeri 1 Angkola Barat which will be carried out in the odd semester of the 2024/2025 school year. The instrument used is a science literacy test instrument that has been validly used. The results of the study showed that the science literacy ability of class XI Phase F students at SMA Negeri 1 Angkola Barat was at a low standard.